2002
DOI: 10.1021/tx0155911
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Characterization of Human Hemoglobin Adducts Formed in Vitro by Hexahydrophthalic Anhydride

Abstract: Primary structural information of anhydride binding to endogenous proteins is of interest in order to determine the mechanism causing the type-I allergy seen in many anhydride-exposed workers. In addition, studies on specific protein adducts may generate new methods for biological monitoring. In this study, the binding of hexahydrophthalic anhydride (HHPA) to human hemoglobin (Hb) in vitro was investigated. The in vitro synthesized conjugates were analyzed using a hybrid quadrupole-time-of-flight mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…Tetrahydrophtalic anhydride (THPA) yields adducts with albumin (Kristiansson, Lindh, & Jonsson Bo, 2003;Kristiansson, Lindh, & Jonsson, 2004) and hemoglobin (Jonsson Bo, Lindh, & Welinder, 1997;Lindh & Jonsson Bo, 1998;Kristiansson, Ajonsson, & Lindh, 2002). The main attachment site was found to be the e-amino group of lysine side chains and the modified amino acid could be isolated from an enzymic digest of hemoglobin with trypsin followed by the unspecific protease pronase E and characterized by fragment ion analysis (Kristiansson, Ajonsson, & Lindh, 2002).…”
Section: Reaction With Chemical Sensitizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrahydrophtalic anhydride (THPA) yields adducts with albumin (Kristiansson, Lindh, & Jonsson Bo, 2003;Kristiansson, Lindh, & Jonsson, 2004) and hemoglobin (Jonsson Bo, Lindh, & Welinder, 1997;Lindh & Jonsson Bo, 1998;Kristiansson, Ajonsson, & Lindh, 2002). The main attachment site was found to be the e-amino group of lysine side chains and the modified amino acid could be isolated from an enzymic digest of hemoglobin with trypsin followed by the unspecific protease pronase E and characterized by fragment ion analysis (Kristiansson, Ajonsson, & Lindh, 2002).…”
Section: Reaction With Chemical Sensitizersmentioning
confidence: 99%
“…The main attachment site was found to be the e-amino group of lysine side chains and the modified amino acid could be isolated from an enzymic digest of hemoglobin with trypsin followed by the unspecific protease pronase E and characterized by fragment ion analysis (Kristiansson, Ajonsson, & Lindh, 2002). A large number of lysine residues of HSA is modified in vitro at 10-fold molar excess of anhydride, while at 0.1-fold only a few positions yielded adducts, the main one being Lys 212 of subdomain IIA (Sennbro et al, 2003).…”
Section: Reaction With Chemical Sensitizersmentioning
confidence: 99%
“…HHP acid was then quantified on an LC/MS/MS (API 3000; Applied Biosystems, Foster City, CA, USA) coupled to an HPLC system from Perkin-Elmer (Norwalk, CT, USA) as described by Kristiansson et al (2002). Briefly, samples were analyzed on a C 18 column (2.1 mm i.d.…”
Section: Quantification Of Hhp Acid By Lc/ms/msmentioning
confidence: 99%
“…After an acid hydrolysis of the protein adducts, the corresponding HHP acid is released. The HHP acid can then be analysed using liquid chromatography tandem MS (LC/MS/MS; Kristiansson et al, 2002) or after derivatization using gas chromatography mass spectrometry (GC/MS; Lindh and Jönsson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that Hb adducts can be used as long-term biomarkers of sensitizing compounds [17,18]. Protein adducts formed by sensitizing chemicals have been characterized in several studies [17,[19][20][21][22][23] using LC/MS/MS or GC/MS. However, the identity of covalent binding sites of acrylates in proteins has not previously been studied.…”
Section: Introductionmentioning
confidence: 99%